Understanding the Interplay between Accounting Practices and Organizational Structures for Strategic Management - Pasolo, Fahrudin (Advances: Jurnal Ekonomi & Bisnis, 2024)
This research aims to investigate the relationship between accounting practices and organizational structures through a qualitative literature review. The research design involves a systematic search strategy to identify relevant literature, followed by data collection from academic databases, journals, and books. Thematic analysis is employed to synthesize and interpret the findings, revealing several key insights. Traditional hierarchical structures are associated with centralized accounting systems, facilitating efficient monitoring and coordination of financial activities. However, decentralization offers flexibility and autonomy, albeit with coordination challenges. Hybrid organizational forms present a balance between efficiency and adaptability. Technological advancements further shape organizational structures and accounting practices, enhancing agility and transparency. The findings underscore the importance of aligning accounting practices with organizational structures to optimize performance. Implications suggest the need for organizations to carefully consider structural and accounting choices to achieve strategic objectives and adapt to market dynamics effectively. Further research should explore the impact of emerging technologies on accounting practices and organizational structures longitudinally.